Effects of inorganic fertilizer on larval development, adult longevity and insecticide susceptibility in the malaria vector Anopheles arabiensis (Diptera: Culicidae). Issue 4 (23rd December 2019) - Samuel, Michael; Brooke, Basil D; Oliver, Shüné V
Abstract: BACKGROUND: Exposure to inorganic fertilizer is common for the major malaria vector Anopheles arabiensis, which is closely associated with agricultural activities. The aim of this study was to understand if insecticide susceptible and resistant individuals respond to fertilizer exposure in the same manner. Two laboratory strains, SENN, an insecticide susceptible strain, and SENN‐DDT, an insecticide resistant strain selected strain selected from SENN, were used in this study. Both strains were exposed to one of three concentrations of a combination nitrogen‐phosphorus‐potassium (NPK) inorganic fertilizer, as well as nitrogenous (urea), phosphorus (superphosphate) and kaelic (potassium chloride, KCl) elemental fertilizer. The time to pupation was monitored, adult longevity was assessed and the insecticide tolerance of adults was determined. The effect of elemental fertilizers on ovipositioning site choice was also assessed. RESULTS: For both strains, urea increased the number of eggs laid, while superphosphate resulted in a significant decrease in egg laying. Larval NPK exposure decreased the time to pupation in the SENN strain but not in SENN‐DDT. Urea exposure increased the time to pupation in both strains, while KCl decreased the time to pupation in both strains. Larval NPK exposure only affected adult male longevity at high concentrations. Larval exposure to NPK and KCl resulted in increased insecticide tolerance in both strains, with variable efficacy from strain to strain. CONCLUSION: Exposure to inorganic fertilizers has a greater effect on insecticide susceptible An. arabiensis as compared to resistant strains, where the primary advantage is increased insecticide tolerance. These data also demonstrate that larval fertilizer exposure can affect fecundity and fertility, and alter the life histories of adult An. arabiensis . © 2019 Society of Chemical Industry Abstract : The larvae of the malaria vector Anopheles arabiensis are often exposed to fertilizer. This article describes the differential effects of inorganic fertilizer exposure on insecticide susceptible and resistant mosquitoes.